2020
DOI: 10.1111/exd.14176
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase is required for epidermal permeability barrier homeostasis in mice

Abstract: Nitric oxide (NO) regulates a variety of epidermal functions, including epidermal proliferation, differentiation and cutaneous wound healing. However, whether nitric oxide (NO) and its synthetic enzymes regulate epidermal permeability barrier homeostasis is not clear. In the present study, we employed inducible nitric oxide synthase (iNOS) KO mice to explore the role of iNOS in epidermal permeability barrier homeostasis. Our results showed that iNOS mice displayed a comparable levels of basal transepidermal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…39,40 However, recent studies by Dang et al demonstrated a need for iNOS in epidermal permeability barrier homeostasis. 22 First, disruption of the epidermal permeability barrier increased expression levels of iNOS mRNA by over onefold in mouse epidermis, consistent with previous findings that barrier disruption increases NO release in the epidermis. 39 While iNOS deficiency delays permeability barrier recovery, topical applications of NO donors largely corrected the permeability barrier F I G U R E 1 Schematic diagram of nitric oxide synthesis abnormality in iNOS knockout mice.…”
Section: Reg Ul Ati On Of Epidermal Perme Ab Ilit Y Barrier By Nosupporting
confidence: 90%
See 3 more Smart Citations
“…39,40 However, recent studies by Dang et al demonstrated a need for iNOS in epidermal permeability barrier homeostasis. 22 First, disruption of the epidermal permeability barrier increased expression levels of iNOS mRNA by over onefold in mouse epidermis, consistent with previous findings that barrier disruption increases NO release in the epidermis. 39 While iNOS deficiency delays permeability barrier recovery, topical applications of NO donors largely corrected the permeability barrier F I G U R E 1 Schematic diagram of nitric oxide synthesis abnormality in iNOS knockout mice.…”
Section: Reg Ul Ati On Of Epidermal Perme Ab Ilit Y Barrier By Nosupporting
confidence: 90%
“…37 A recent study demonstrated an elevation in iNOS mRNA expression following acute disruption of the epidermal permeability barrier. 22 In addition to enzymatic production of NO, non-enzymatic decomposition of photo-reactive nitrogen oxides can produce NO in the skin. For example, UVA irradiation (40 J/cm 2 ) of either human skin or skin homogenates can increase NO content by ≈90%.…”
Section: Produc Tion and Reg Ul Ation Of Nitric Oxidementioning
confidence: 99%
See 2 more Smart Citations
“…Barrier disruption was achieved by repeated applications of cellophane tape to both flanks of mouse skin until ≥2-fold increase in transepidermal water loss rates (TEWL), measured with a TM300 probe connected to MPA580 (C&K). 12 Skin samples were collected from mice without tape-stripping and 1 h after tape-stripping. The epidermis was separated from the dermis by heat separation as described previously.…”
Section: Animals and Proceduresmentioning
confidence: 99%